Cape Verde : 2006 Article IV Consultation and Request for a Three-Year Policy Support Instrument-Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cape Verde. (IMF Staff Country Reports; Country Report ;, 2006)
Cape Verde's economic and policy performance remains sound under the Poverty Reduction and Growth Facility (PRGF) arrangement supported by Policy Support Instrument (PSI). Executive Directors commended the prudent macroeconomic policies and structural reforms. They emphasized the need for strengthening economic management through building capacity in fiscal management and policy formulation. They advised that particular attention should be given to improving the public sector and regulatory reforms, and strengthening the regulatory framework for the energy and financial sectors.